Washatiyyah Theology And Religious Moderation - Basri Basri; Indo Santalia (Journal of Innovative and Creativity, 2025)
This research examines the theological foundations of washatiyyah and its relationship with contemporary religious moderation discourse and practice within Muslim communities. Through qualitative library research employing descriptive-analytical approaches, this study explores classical Islamic sources establishing washatiyyah as a comprehensive theological principle rooted in Quranic teachings and prophetic traditions. The investigation reveals that washatiyyah encompasses multiple dimensions including moderation in belief, worship, ethics, and social interactions, providing indigenous Islamic resources for articulating authentic moderate religiosity. Analysis demonstrates that washatiyyah theology offers effective responses to religious extremism by challenging the selective interpretation, decontextualized application, and absolutist thinking characterizing extremist ideologies. The research identifies significant convergence between washatiyyah principles and contemporary religious moderation initiatives while acknowledging tensions regarding specific applications in modern contexts. Findings indicate that successful implementation of washatiyyah requires systematic integration into religious education, community discourse, and institutional policies, with particular attention to youth engagement and digital dissemination strategies. The study concludes that washatiyyah theology provides sustainable foundations for religious moderation that resonate with Muslim communities due to authentic grounding in Islamic tradition rather than appearing as externally imposed constructs. However, effective application demands sophisticated interpretation addressing unprecedented modern challenges through qualified scholarship combining deep Islamic knowledge with contextual awareness. This research contributes to academic discourse on Islamic theology, religious moderation, and counter-extremism while offering practical guidance for educators, religious leaders, policymakers, and community organizations promoting peaceful coexistence and balanced religiosity in pluralistic contemporary societies.